The Influence of Infant and Child Feeding Counseling (PMBA) on Mother's Knowledge and Practices and The Growth Status af Baduta in The Kebayoran Lama Area, South Jakarta - Rahmawati, Siti Mutia; Meilinasari, Meilinasari; Marbun, Rosmida (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2025)
70% of the energy needs of infants aged 6-9 months are met by breast milk, 50% of the energy needs of 9-12 months are still met by breast milk, and only 30% of the energy needs of 12-24 months are met by breast milk. Complementary foods can meet the energy needs of infants and children aged 6-24 months. The introduction and provision of MP-ASI must be done gradually, both in terms of form and quantity. However, the results of the study found that in children aged 6-24 months, 2 out of 3 children did not receive adequate Complementary foods, and only 39.8% of children aged 6-24 months received adequate Complementary foods. The purpose of this study was to analyze the effect of PMBA counseling in improving mothers' knowledge and practices and toddler growth status. This study design was a quasi-experimental study, pre- and post-treatment groups, to determine the effect of PMBA counseling on mothers' knowledge and practices of PMBA and toddler growth status. This study was conducted in September-November 2022, involving 31 mothers of toddlers aged 6-24 months. The results of the study showed that counseling could improve knowledge and PMBA practices of mothers of 6-24-month-old toddlers, as well as the growth status of toddlers after PMBA counseling was given, with a value (p<0.05).